Effect of seed drying temperature on subsequent seed longevity of soya bean genotypes harvested at different stages of seed maturation - Salvador, O.F. (University of Reading, 2024)
It is recommended that seeds destined for long-term storage in genebanks be dried first to low moisture content at 10-15% RH, 10-25°C, but in some crops, an initial warmer drying temperature could be better. Seeds of diverse accessions of soya bean (Glycine max (L.) Merr.) were grown in three seasons and harvested shortly before and at harvest maturity, then dried initially for 4 days at 17, 30 or 40°C with 15% RH, fumigated before or after this treatment, and subsequently dried at 17°C with 15% RH to final equilibration to low moisture content. Seed longevity was then determined by artificial ageing at 45°C and 60% RH (approximately 9% moisture content). Seed longevity was affected by the initial treatments, but effects varied among treatment combinations and accessions. Seeds harvested before harvest maturity, at 10-14% moisture content, tended to benefit from warmer temperature drying. On average, fumigation before drying (current IITA protocol) resulted in shorter longevity than fumigation after initial drying; this effect was more pronounced with warmer temperature drying. Most treatment combinations across all three experiments showed seed longevity was improved, often considerably, by initial drying at 40°C compared to drying at 17°C throughout and in many, but fewer, treatment combinations, longevity was also improved by drying at 30°C compared to 17°C. In some of the treatment combinations, however, longevity was reduced by drying at 40°C or at 30°C compared to 17°C. This research has provided evidence of a potential benefit to subsequent seed longevity from initially drying soya bean seeds at 40°C, rather than 10-25°C, for most accessions.